Theorizing with managers: how to achieve both academic rigor and practical relevance? - Nenonen, Suvi; Brodie, Roderick J.; Storbacka, Kaj; Peters, Linda D. (Emerald, 2017)
Purpose. There are heightened concerns that the theory-praxis gap is widening, despite decades of academic literature addressing the issue. We propose that one viable solution to this challenge is involving practitioners in research processes as active, reflective and empowered participants. Most extant discussions addressing the inclusion of managers as partners in theorizing restrain themselves to an ‘if’ question, arguing whether or not it is possible to create sufficiently rigorous knowledge in collaboration with practitioners. This leaves the ‘how’ question unanswered, i.e., how should such gap-bridging research be conducted in practice. Thus, the aim of this paper is to investigate how academic researchers in management and marketing can theorize with managers in order to generate results that are both academically rigorous and managerially relevant. Design/methodology/approach. Based on a literature review of collaborative theorizing processes, we develop a conceptual framework highlighting the main research design decisions when theorizing with managers. The use of the framework is illustrated with four research program examples. Findings. Most accounts of theorizing with managers use – explicitly or implicitly – abduction as the main mode of inference. In addition to this philosophical commonality, our literature review identified twelve themes that should be considered when designing collaborative research processes. The four illustrative examples indicate that theorizing with managers is an effective way of producing and socializing both academically sound and managerially relevant knowledge. On the other hand, collaborative theorizing processes are time-consuming and studies using abductive reasoning may be more challenging to publish in top-tier journals. Originality/value. This paper makes two contributions. First, we go beyond the extensive academic literature which provides a plethora of explanations and ideas for potential remedies for bridging the theory-praxis gap by offering a detailed description how one particular solution, theorizing with managers, unfolds in practice. Second, we ground collaborative theorizing processes in the philosophy of science and put abduction forward as a common nominator for such studies.